2022
DOI: 10.3389/fendo.2022.934003
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of euthyroidism with levothyroxine: implications of etiology of hypothyroidism and the degree of residual endogenous thyroid function

Abstract: There are many thyroid-related factors that combine with non-thyroid-related factors in order to affect the patient response to treatment of hypothyroidism, in terms of their satisfaction with therapy. Some of the thyroid-derived factors include the etiology of the hypothyroidism and the amount of residual thyroid function that the patient retains. These two factors may be intertwined and affected by a third influence, the presence of thyroid peroxidase antibodies. The downstream consequences of the interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Low serum FT3 levels and low FT3/FT4 ratios with LT4 treatment would suggest tissue hypothyroidism, which could - at least in part - explain persisting hypothyroid symptoms and would contradict the hypothesis that local deiodinases always convert T4 into sufficient T3 levels [30] , [45] . Several authors believe that, although LT4 replacement restores (hypothalamic) TSH concentrations, it may in fact not fully restore euthyroidism at the tissue or receptor level [30] , [41] , [46] , [47] , [48] , [49] . Our data might fit with this ‘low T3 ' hypothesis to explain persisting symptoms, since low serum FT3 concentrations were reported concurrent with low FT3/FT4 ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Low serum FT3 levels and low FT3/FT4 ratios with LT4 treatment would suggest tissue hypothyroidism, which could - at least in part - explain persisting hypothyroid symptoms and would contradict the hypothesis that local deiodinases always convert T4 into sufficient T3 levels [30] , [45] . Several authors believe that, although LT4 replacement restores (hypothalamic) TSH concentrations, it may in fact not fully restore euthyroidism at the tissue or receptor level [30] , [41] , [46] , [47] , [48] , [49] . Our data might fit with this ‘low T3 ' hypothesis to explain persisting symptoms, since low serum FT3 concentrations were reported concurrent with low FT3/FT4 ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies observed delayed gastric emptying ( Pfaffenbach et al, 1997 ; Gharahbaghian et al, 2007 ). Euthyroidism restoration results in slightly increased gastric emptying rate ( Jonklaas, 2022 ). Hyperthyroidism treatment may improve abnormal myoelectrical activity and GI symptoms ( Gunsar et al, 2003 ).…”
Section: Hyperthyroidism and Gi Motilitymentioning
confidence: 99%
“…Data indicate that L-thyroxine therapy can improve the symptoms of gastric dysmotility that are apparent in the subclinical hypothyroidism (SCH) state. Hypothyroid patients are routinely treated worldwide with levothyroxine sodium monotherapy in replacement mode ( Jonklaas, 2022 ). There has been strong suggestion for an individually tailored dose ( Yin and Chen, 2013 ).…”
Section: Clinical Manifestations Associated With Changes In Gi Motilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This enigmatic condition, also referred to as “syndrome T” 5 , 8 or “syndrome of residual symptoms of hypothyroidism on T4” (SORSHOT) 9 affects about 0.5% of the inhabitants of developed countries 2 . A plethora of possible underlying mechanisms have been suggested, including psychological factors, the presence of other autoimmunity diseases, thyroid autoimmunity, insufficient dosage, hysteresis effects, the modality of therapy with levothyroxine (potentially resulting in abnormal T3 generation) and polymorphic variants of deiodinase genes 2 , 10 12 .…”
Section: Introductionmentioning
confidence: 99%